2020
DOI: 10.1097/dcr.0000000000001787
|View full text |Cite
|
Sign up to set email alerts
|

Recurrence of Acute Right Colon Diverticulitis Following Nonoperative Management: A Systematic Review and Meta-analysis

Abstract: BACKGROUND: There are currently no guidelines on the management of right colon diverticulitis. Treatment options have been extrapolated from the management of left-sided diverticulitis. Gaining knowledge of the risk and morbidity of diverticulitis recurrence is integral to weighing the benefit of elective surgery for right-sided diverticulitis. OBJECTIVE: The purpose of this study was to summarize the recurrence rate and the morbidity of recurrence of H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…Stratified by the location, the cumulative recurrent rates in right-sided diverticulitis was 8%, 46% in the descending colon, and 68% in the sigmoid colon (Tale 2). As compared with the meta-analysis conducted by Lee et al, the recurrence rate of right-sided diverticulitis was relatively lower (12% in the meta-analysis) 17 . One of the possible reasons is ethnicity.…”
Section: Discussionmentioning
confidence: 55%
“…Stratified by the location, the cumulative recurrent rates in right-sided diverticulitis was 8%, 46% in the descending colon, and 68% in the sigmoid colon (Tale 2). As compared with the meta-analysis conducted by Lee et al, the recurrence rate of right-sided diverticulitis was relatively lower (12% in the meta-analysis) 17 . One of the possible reasons is ethnicity.…”
Section: Discussionmentioning
confidence: 55%
“…The first study[ 60 ] focused on the fact that only 4.4% of recurrences were complicated and there was only a 1.7% of re-recurrence rate. While the second[ 61 ] showed that only a small percentage of patients underwent surgery after recurrence (9.9% as urgent cases, 5.4% as elective cases). Both authors conclude that NOM is safe and feasible for Hinchey 1b-2 stages, similarly to the management of uncomplicated left-sided diverticulitis, while surgery should only be performed in selected cases.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] Similar to the more common sigmoid diverticulitis, nonoperative treatment methods are preferred for the vast majority of patients presenting with uncomplicated disease. [2][3][4] Albeit acute RCD tends to present a lower rate of complicated disease than left-sided diverticulitis, surgical resection is generally used in the treatment of complicated cases owing to a high recurrence rate ( > 60%) and a significant risk of developing local complications such as fistula, chronic abscess, and stenosis. 4,5 Though surgery for acute RCD is currently safer than in the past, the right-sided disease is still associated with significantly higher mortality among patients undergoing colectomy for acute diverticulitis.…”
Section: Introductionmentioning
confidence: 99%